PENGARUH JARAK TANAM DAN PEMBERIAN PUPUK KANDANG LEMBU TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG KEDELAI (Glycine max (L) Merril) - Novilda Elizabeth Mustamu (JURNAL AGROPLASMA, 2019)
The method used is a randomized block design (RBD) with 12 factorial combinations of treatments and 3 replications, Cow manure factor consists of 4 levels, namely: K1 = 10 kg / plot, K2 = 15 kg / plot, K3 = 20 kg / plot, K4 = 25 kg / plot, while the planting distance factors consists of 3 levels, namely: J1 = 20 x 30 cm, J2 = 20 x 40 cm, J3 = 20 x 50 cm. There are 5 parameters observed, namely plant height (cm), number of leaves (pieces), flowering (days), production of planting seed sample (g), seed production per plot (g). The Cow manure and planting distance treatment showed very significant effect on the parameters flowering, seed production per plant samples, and production of seeds per plot, while there was no significant influence on the parameters of plant height and number of leaves. treatment plant award distance showed a significant influence on the parameters of plant height and flowering date, but there was also a significant effect on production parameters of seeds per plant and seed production samples per plot. While there was no significant effect on the parameters of the number of leaves. Interaction cow manure and planting distance effect was not significantly affected all parameters were observed. Keywords : Cow Manure, Planting Distance, Glycine max (L) Merril